The Pharmacological and Structural Basis of the AahII–NaV1.5 Interaction and Modulation by the Anti-AahII Nb10 Nanobody - Hmaidi, Riadh; Ksouri, Ayoub; Benabderrazek, Rahma; Antonietti, Viviane; Sonnet, Pascal; Gautier, Mathieu; Bouhaouala-Zahar, Balkiss; Ouadid-Ahidouch, Halima (Frontiers in Pharmacology, 2022)
Scorpion α-toxins are neurotoxins that target the fast inactivation mechanism of voltage-gated sodium (NaV) channels leading to several neuro- and cardiotoxic effects in mammals. The toxin AahII is the most active α-toxin from the North African scorpion Androctonus australis Hector that slows the fast inactivation of NaV channels. To fight scorpion envenomation, an anti-AahII nanobody named NbAahII10 (Nb10) was developed. The efficiency of this nanobody has been evaluated in vivo on mice but its mechanism of action at the cellular level remains unknown. Here we have shown that AahII toxin slows the fast inactivation of the adult cardiac NaV1.5 channels, expressed in HEK293 cells, in a dose-dependent manner, while current amplitude was not affected. The inactivation of NaV1.5 is slower by a factor of 4, 7, and 35 in the presence of [AahII] at 75 nM, 150 nM, and 300 nM, respectively. The washout partially reversed the toxin effect on inactivation from 8.3 ± 0.9 ms to 5.2 ± 1.2 ms at 75 nM. We have also demonstrated that the highly neutralizing Nb10 can fully reverse the effect of AahII toxin on the channel inactivation kinetics even at the 1:1 molar Ratio. However, the 1:0.5 molar Ratio is not able to neutralize completely the AahII effect. Therefore, the application of Nb10 promotes a partial abolishment of AahII action. Bioinformatic analysis and prediction of NaV1.5 driven docking with AahII show that Ala39 and Arg62 of AahII play a crucial role to establish a stable interaction through H-bound interactions with Gln1615 and Lys1616 (S3–S4 extracellular loop) and Asp1553 (S1–S2 loop) from the voltage-sensing domain IV (VSD4) of NaV1.5, respectively. From this, we notice that AahII shares the same contact surface with the Nb10. This strongly suggests that Nb10 dynamically replaces AahII toxin from its binding site on the NaV1.5 channel. At the physiopathological level, Nb10 completely neutralized the enhancement of breast cancer cell invasion induced by AahII. In summary, for the first time, we made an electrophysiological and structural characterization of the neutralization potent of Nb10 against the α-scorpion toxin AahII in a cellular model overexpressing NaV1.5 channels.